IMPROVEMENT OF THE RADIATION DIAGNOSIS OF ASEPTIC NECROSIS OF THE FEMORAL HEAD IN PERSONS WITH POSTCOVID SYNDROME (World Bulletin of Public Health, 2024)
Osteonecrosis is a severe disabling disease that often develops in people of young working age (the average age is 33-45 years) and is associated with the death of bone cells in a certain area of bone tissue, usually provoked by a violation of local blood supply. IT most often develops in the head of the femur, the condyles of the femur and tibia are indicated in second place in terms of the frequency of lesion, the head of the humerus, talus, etc. It is customary to distinguish idiopathic (primary) and secondary IT. The latter is associated with specific causal factors and is more common than the primary one. Risk factors for the development of secondary ON of the femoral head are, for example, considered to be: traumatic damage to the hip joint, surgical interventions on it, hip dysplasia, immuno-inflammatory rheumatic diseases, various coagulopathies, hyperlipidemia, genetic abnormalities, chronic liver diseases, treatment with glucocorticoids (HA), radiation and polychemotherapy, alcohol abuse and a number of others.
Keywords: aseptic bone necrosis; osteonecrosis; coronavirus infection